Dilemmas experienced by the nursing team in patient care with COVID-19 in the ICU: Integrative review (Research, Society and Development, 2021)
Objective: To identify and analyze the scientific evidence available in the literature on the dilemmas experienced by the nursing staff in patient care with COVID-19 in the ICU. Methodology: This is an integrative review research, meeting the PRISMA recommendations and developed in six stages: 1) identification of the theme and formulation of the guiding question; 2) literature search; 3) categorization of studies; 4) evaluation of included studies; 5) interpretation of results; 6) knowledge synthesis. Results: The search in the databases: Scopus; Embase, ScienceDirect, Lilacs, Nursing Database - BDENF, PubMed Central, MEDLINE, Web of Science and Cinahl. Published from January 2020 to April 2021. The search reached 248,900 articles, from which five articles that met the established criteria were selected. The dilemmas identified in the literature were the shortage of qualified and specialized labor, lack of personal protective equipment, abusive workloads, stress and fear, poor communication with the patient, physical and emotional exhaustion. Conclusion: It is considered extremely important to highlight this reality and seek strategies that favor the reduction of dilemmas experienced by nursing professionals who provide nursing care to patients with COVID-19 in the ICU.